Biochemical and plasma lipid responses to pemafibrate in patients with primary biliary cholangitis. Issue 10 (14th June 2019) - Joshita, Satoru; Umemura, Takeji; Yamashita, Yuki; Sugiura, Ayumi; Yamazaki, Tomoo; Fujimori, Naoyuki; Matsumoto, Akihiro; Tanaka, Eiji
Abstract : Aim: Fibrate addition to ursodeoxycholic acid (UDCA) therapy has been shown to improve both liver biochemistry and long‐term prognosis in primary biliary cholangitis (PBC) patients showing an incomplete biochemical response to UDCA alone. We herein describe the clinical outcome of seven cases of PBC that received the new selective peroxisome proliferator‐activated receptor α modulator, pemafibrate, in combination with UDCA therapy to investigate the biochemical and plasma lipid responses to the drug. Methods: Of 124 initially enrolled PBC patients, 12 treated with UDCA alone and seven receiving UDCA plus bezafibrate showed alkaline phosphatase (ALP) levels above the upper limit of normal (330 U/L). Ultimately, seven patients with PBC and dyslipidemia who had agreed to biweekly visits at our hospital for UDCA plus pemafibrate combination therapy were retrospectively analyzed. Results: In the four cases that switched from bezafibrate to pemafibrate, ALP became significantly decreased (0.031) and γ‐glutamyltransferase tended to decrease (0.063) over the 3 months following pemafibrate addition. Two patients showed a greater than 50% reduction in ALP. No remarkable differences were observed for plasma lipid levels, alanine aminotransferase, aspartate aminotransferase, or the liver fibrosis marker Mac‐2 binding protein glycosylation isomer between these time points. No adverse drug reactions were recorded. Conclusions: Pemafibrate might be another option for PBC patients with an incomplete response to UDCA therapy.